Advanced thermoplastic carbon fibre reinforced pultruded composites - Novo, P. J. (2014)
The aim of this work is to optimize the production of new continuous carbon fibers reinforced thermoplastic matrix pre-impregnated materials (towpregs) continuously processed by dry deposition of polymer powders in a new equipment developed by the Institute for Polymers and Composites (IPC). The processing of the produced towpregs by pultrusion, in a developed prototype equipment existing in the Engineering School of the Polytechnic Institute of Porto (ISEP), was also optimized. Two different thermoplastic matrices were studied: one for commercial applications (polypropylene) and an-other for advanced markets (Primospire®). The optimization was made by studying the influence of the most relevant processing parameters in the final properties of the produced towpregs and composites. The final pultruded composite profiles were submitted to mechanical tests in order to obtain relevant properties.